Economic Survey of Oil Palm Products’ Processing and Marketing in Kogi State, Nigeria - Ojonimi Onoja, Anthony; Ogali, T. U. (Consilience, 2015)
This study was designed to ascertain the level of profitability and inherent problems derivable from oil palm products’ processing and marketing in Kogi State of Nigeria. Primary data used for the study was obtained through the use of structured questionnaire and oral interviews. From the six agricultural Zones in Kogi State a total sample size of 60 was finally drawn to form the sampling frame from 3 Agricultural Zones. Descriptive statistics were used to attain objectives 1 and 3; while objective 2 was attained by the use of gross margin analysis. Majority of the farmers obtained their Fresh Fruit Bunches for processing from the village or open market (50%); oil palm processing and marketing is profitable business in the area with a gross margin of N603,320.00K and gross margin ratio of 2.72 from an average enterprise; problems identified in the enterprises included fluctuating prices, lack of basic infrastructure and inputs such as capital and processing machines. The study recommended the need for government to hasten the supply of rural infrastructure, reduce taxes and let processors/marketers be encouraged to form cooperatives so as to access credit.